PENERAPAN PROSEDUR AUDIT INTERNAL PEMBERIAN KREDIT PADA PT. BANK SULSELBAR CABANG SELAYAR - Sintya Kartika Angelina; H. Andi Jam'an; Ainun Arizah (P3M- Politeknik Negeri Kupang, 2023)
This study aims to describe how the application of internal audit procedures for granting credit at PT. Selayar branch of Bank Sulselbar. The type of data used in this study is qualitative data obtained from interviews and informants related to the problem under study. Data collection is done by observation and interviews. In this study, the data sources used in data collection include primary data and secondary data. The results showed that the application of internal audit procedures for granting credit at PT. Bank Sulselbar Selayar branch has disbursed loans in accordance with established provisions and procedures, starting from the introduction and approach to prospective debtors, the credit application stage, data identification. After identifying the data by the credit department, it can be considered for approval or rejection with the aim of avoiding the risk of bad credit.